Efektifitas Short Movie untuk Meningkatkan Critical Thinking dalam Pembelajaran Mahārah Kitābah - Hani’atul Khoiroh; Mohammad Makinuddin; Abdullah Sarif; Asma Rosyidah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
This study aims to examine the effect of using Sirah Nabawiyah short movies on the improvement of students’ critical thinking skills in maharah kitābah (Arabic writing skills). The research employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The participants consisted of 30 students of MTs. Mambaus Sholihin Suci Manyar Gresik, selected through simple random sampling. Data were collected using a written test developed based on critical thinking indicators, including analytical, evaluative, inferential, and logical reasoning skills. The data were analyzed using a paired sample t-test with the assistance of SPSS version 25. The results showed an increase in the students’ mean scores from 60.66 in the pretest to 83.66 in the posttest. The statistical analysis revealed a significance value of 0.000 (< 0.05), indicating a statistically significant difference in students’ critical thinking skills before and after the treatment. These findings suggest that the use of short movies effectively stimulates higher-order thinking skills, particularly in strengthening students’ critical thinking abilities.